Is Lysyl Oxidase-Like Protein-1, Alpha-1 Antitrypsin, and Neutrophil Elastase Site- Specific in Pelvic Organ Prolapse? - Man, Weng-Chi (2009)
The expression level of elastin metabolism-related proteins is variable in the vagina and does not correlate with the most prominent area of prolapse. INTRODUCTION: We investigated whether the expression of alpha-1 antitrypsin (ATT), neutrophil elastase (NE) and lysyl oxidase-like protein 1 (LOXL-1) vary within the vagina in subjects with pelvic organ prolapse (POP). METHODS: Biopsies were obtained from the anterior and posterior vaginal wall of 22 women with POP (≥ stage 2 by POP-Q). The subjects were grouped by the most prominent defect: cystocele, cystocele plus uterine prolapse, and rectocele. Comparative real-time PCR, Western blotting, and NE enzyme activity assay were performed. RESULTS: The ratio of anterior and posterior vaginal wall ATT, NE, and LOXL-1 expression varied between individuals within the same defect group. CONCLUSIONS: ATT, NE, and LOXl-1 expression was variable among different biopsy sites in the vagina. No consistent pattern was present when the subjects were grouped by the most prominent defect. We recommend careful consideration of biopsy sites in future studies on POP to enhance reproducibility of data.